STRATEGI PENINGKATAN KESEJAHTERAAN NELAYAN KECIL DI DESA TOKKE KECAMATAN MALANGKE KABUPATEN LUWU UTARA - Aqidah Husain; Rustam Rustam; Ernaningsih Ernaningsih (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
This research was conducted with the aim of (1) Identifying the socio-economic characteristics of small fishermen, (2) Analyzing the welfare level of small fishermen, (3) Formulating strategies to improve the welfare of small fishermen in Tokke Village, Malangke District, North Luwu Regency. This study was analyzed based on each objective. The first objective was analyzed by descriptive analysis using the interview method, questionnaire, documentation and direct observation supported by two data, primary and secondary data. Respondents in this study were all small fishermen in Tokke Village and informants who were considered to know the most problems faced by fishermen in the field. The second objective is analyzed by combining income analysis and welfare indicator analysis, while the third objective is analyzed by the SWOT analysis method. The results showed that fishermen's socioeconomic characteristics were influenced by fishermen's income, fishermen age, education level, fishing facilities and infrastructure used by fishermen. The level of welfare of small fishermen in Tokke Village, Malangke Subdistrict, North Luwu Regency, as many as 34% of fishing households have a low welfare level and 66% of fishermen households are at moderate welfare level. Some SWOT analysis strategies are found from various internal and external factors related to improving the welfare of small fishermen, namely the utilization of potential fishery resources, the development of alternative businesses, the development of facilities and infrastructure of the coastal area, alternative livelihoods, development of capital systems, utilization of existing production into processed products. through human resource development.